Camellia Sinensis Leaves Hydroalcoholic Extract Improves the Alzheimer's Disease-Like Alterations Induced by Type 2 Diabetes in Rats - ÇAM, MUHAMMET EMİN; TAŞKIN, TURGUT (MARMARA UNIV, INST HEALTH SCIENCES, 2020)
Objective: Novel investigations have confirmed that hyperglycemia is strictly associated with the development of cognitive impairment and dementia. Sodium-dependent glucose transporter (SGLT) inhibitors, which are oral antidiabetic drugs, are currently being investigated as the medication in Alzheimer's disease (AD). In our study, Camellia sinensis (green tea), which inhibits sodium-dependent glucose transporter-1 (SGLT-1), was used in the treatment of type 2 diabetes mellitus (T2DM)-induced AD-like alterations via its antidiabetic effects. Methods: High-fat diet/streptozotocin-treated rat model was chosen to provide T2DM-induced AD-like alterations. Antidiabetic effects were evaluated with the measurement of blood glucose level (BGL), oral glucose tolerance test (OGTT), and insulin tolerance test (ITT). On the other hand, novel object recognition test (NORT), open field test (OFT), passive avoidance test (PAT), and Morris's water maze (MWM) test were performed to investigate the anti-Alzheimer's effects of C. Sinensis. Results: C. sinensis tolerated BGL for a short time but metformin, the first medication prescribed for T2DM, tolerated BGL during the test for 120 min. C. sinensis increased the number of square crosses and the frequency of grooming activity in a similar manner to metformin in OFT. C. sinensis treatment improved exploratory behavior and memory retention components in NORT. The step-through latency decreased in HFD/STZ-treated rat model but it improved with metformin and C. sinensis treatment in PAT. According to the results obtained by the MWM test, C. sinensis treatment slightly improved learning. Conclusion: C. sinensis improved short-term memory and increased the locomotor activity in rats according to the results obtained by NORT, OFT, and PA.
Keywords: Camellia sinensis; sodium-dependent glucose transporter; diabetes mellitus; Alzheimer's disease; memory; HIGH-FAT DIET; MEMORY IMPAIRMENTS; PATHOGENESIS; MECHANISMS; METFORMIN; BRAIN; DRUGS; RISK